Suitability of two WHO research and development initiatives for COVID-19 to promote equitable innovation: the Access to COVID-19 Tools Accelerator and COVID-19 Technology Access Pool - Luiza Pinheiro Alves da Silva; Márcia Siqueira Rapini (Pan American Health Organization, 2022)
Objectives. To analyze the World Health Organization's (WHO's) contribution to promotion of access to innovative technologies by assessing its initiatives on coronavirus disease 2019 (COVID-19) research, development, and innovation. Methods. A document search was done for previous criteria used by WHO working groups to evaluate innovation and access merits. Two sets of criteria were identified. One set was used to assess the suitability of existing mechanisms to coordinate research, development, and innovation and pool funds globally. The second set was used to measure success in implementing demonstration projects and consider the extent of innovative components being implemented by them. These criteria were applied to the COVID-19 Technology Access Pool (C-TAP) and Access to COVID-19 Tools Accelerator (ACT-A) initiatives. Scores were classified as: meets the criteria (2); partially meets the criteria (1); does not meet the criteria (0). Results. Both initiatives met all the first set of criteria. C-TAP, an initiative based on a patent pool and other open knowledge approaches, best met the second set of criteria, scoring 7 out of 12 points. ACT-A, based on pooled funds, advanced purchase agreements, and voluntary contributions, met none of the second set of criteria. Conclusions. Equitable access to health technologies has been a recurring problem in recent pandemics and initiatives were proposed to prevent it. However, even though COVID-19 has been the greatest health crisis in the 21st century, market dynamics still prevailed. Income disparities between countries and lack of support for solidarity and a global health approach only aggravated the negative health and economic impacts.